The bad mood and the stick [book with audioplayer] - Snicket, Lemony ([Library Ideas, LLC], 2018)
New York Times bestselling author Lemony Snicket sheds light on the way bad moods come and go. Once there was a bad mood and a stick. The stick appeared when a tree dropped it. Where did the bad mood come from? Who picked up the stick? And where is the bad mood off to now? You never know what is going to happen.